1988
DOI: 10.1111/j.1476-5381.1988.tb11533.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenylamine on single ventricular myocytes of guinea‐pig

Abstract: 1 The action of prenylamine, an antianginal drug, was studied in single ventricular guinea-pig myocytes. In concentrations of 10-50 pm, prenylamine significantly (P <0.01) shortened action potentials, and significantly (P < 0.001) reduced the inward calcium current by 29% to 76% (n = 7). This effect was also present in the presence of adrenoceptor-blockade (with phentolamine and propranolol), and was thus not due to indirect changes in endogenous catecholamine action. 2 Prenylamine did not affect the steady st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 22 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Although this agent is associated with torsade de pointes , 92 it appears to mediate its pro‐arrhythmic effects via a calcium‐dependent, rather than potassium‐dependent, mechanism. 93 With rapid stimulation rates, prenylamine is associated with block of calcium channels but, at low stimulation rates, prenylamine acts as an agonist to calcium channels (possibly a stereoselective action mediated by the + isomer), which can lead to calcium channel reactivation and EAD. 92 Although unusual, this observation suggests that while acquired LQTS commonly correlates with I Kr /HERG blocking actions, this may not always be the underlying basis for pro‐arrhythmia.…”
Section: Acquired Lqts and Pharmacological Inhibition Of Ikrmentioning
confidence: 99%
“…Although this agent is associated with torsade de pointes , 92 it appears to mediate its pro‐arrhythmic effects via a calcium‐dependent, rather than potassium‐dependent, mechanism. 93 With rapid stimulation rates, prenylamine is associated with block of calcium channels but, at low stimulation rates, prenylamine acts as an agonist to calcium channels (possibly a stereoselective action mediated by the + isomer), which can lead to calcium channel reactivation and EAD. 92 Although unusual, this observation suggests that while acquired LQTS commonly correlates with I Kr /HERG blocking actions, this may not always be the underlying basis for pro‐arrhythmia.…”
Section: Acquired Lqts and Pharmacological Inhibition Of Ikrmentioning
confidence: 99%
“…A number of investigators had studied the electrophysiological properties of prenylamine. [8][9][10][11][12] In order to explore further its bradycardic, negative inotropic and torsadogenic effects, de Bonfioli Cavalcabò and colleagues 12 studied its electrophysiological activities in great detail and reported that prenylamine was able to abolish early after depolarizations (EADs) which can trigger arrhythmias such as torsade de pointes (TdP). They concluded that prenylamine had an intriguing in vitro electrophysiological profile, making it difficult to extrapolate these in vitro findings to its in vivo pharmacology.…”
Section: Chemistry Pharmacology and Electrophysiologymentioning
confidence: 99%